Democracy Without Choice: A Legal Evaluation of the 2024 Banjarbaru Regional Election - Adelia, Nisa; Maulana, Akhmad; Lestari. MS, Habibah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The phenomenon of a single candidate and the absence of a blank vote option in the 2024 Banjarbaru local election has raised serious concerns about the quality of local democracy in Indonesia. Although legally valid, the limited political choice reflects a degradation of democratic substance and threatens public trust. This study aims to analyze the legal and political dynamics surrounding the case and to evaluate the legal mechanisms in place to safeguard the quality of democracy. This research uses a normative legal method with a case study approach, supported by qualitative analysis of legislation and Constitutional Court decisions. The findings indicate that elections without genuine alternatives violate the principles of participation and contestation as proposed in Robert A. Dahl's theory of polyarchy and contradict the values of public interest as outlined in Jasser Auda’s concept of maqasid shariah. Although the Constitutional Court ordered a re-vote, the legitimacy of the election process had already been undermined. In conclusion, lawful procedures alone are insufficient to ensure a fair democracy if they are not implemented inclusively and participatively. A thorough evaluation of regulations and institutional integrity is necessary to ensure that democracy is not merely procedural, but also substantive.